(3GdTLQI GdfYeGfjI aj GdOhdI GdYKeGfjIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfj PGcQ aj gPg GdQSGdI eG OYJ GdMGLI Edjg ef PcQ MhGOK GdReGf GdoefHYKI s
(3BNQgG (B:s
(3MJi jJe YGe GdUGO hGdCda GdbGFe HGdeQUGO hJQO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B41s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs